Potency of Endo-Exopolysaccharide from Porphyridium cruentum (S.F.Gray) Nägeli as Antioxidant (DPPH) and Biological Toxicity (BSLT) - Agustini, Ni Wayan Sri; ., Kusmiati (KnE Life Sciences, 2017)
Sources of antioxidants are abundant in nature, one of which is derived from microalgae. Microalgae species that have potentially to be developed as a producer of antioxidant compounds is Porphyridium cruentum (S.F.Gray) Nägeli. P. cruentum is a red microalga (Rhodophyceae) and has been known as polysaccharides producer (exopolysaccharide and endopolysaccharide) and as an antioxidant. This study aims to determine antioxidant activity of the extracts and biological toxicity of endo- and exopolysaccharide P. cruentum. The antioxidant activity use reduction method of free radicals (DPPH), whereas toxicity uses Brine Shrimp Lethality Test. (BSLT). The result shows that there is an antioxidant activity with IC50 value of 50.586 5 mg · kg–1 (exopolysaccharide) and 145.998 8 mg · kg–1 (endopolysaccharide). In addition, the result indicates the toxic nature of the Artemia salina Leach. with LC50 values of 513.175 1 mg · kg–1 (exopolysaccharide) and 521.823 3 mg · kg–1 (endopolysaccharide). Therefore, endo- and exopolysaccharide produced by P. cruentum suitable to be used as an alternative source of natural antioxidants and potential for further developed as antitumor drugs. Keywords: antioxidant, biological toxixity, endo-exopolysaccharide, Porphyridium cruentum (S.F.Gray) Nägeli.